A Robust, Moisture- and Air-Stable Phosphine Mono-Ylide Palladacycle Precatalyst: A Simple and Highly Efficient System for Mizoroki–Heck Reactions - Sabounchei, Seyyed Javad; Ahmadi, Mohsen; Azizi, Tayebeh; Panahimehr, Mohammad (Synlett, 2014)
A palladacycle phosphine mono-ylide complex was identified as an efficient catalyst system for the Mizoroki–Heck cross-coupling reactions of aromatic or aliphatic olefins with a variety of aryl bromides and chlorides, including those containing electron-donating or electron-withdrawing substituents. The reactions, which proceeded in moderate to excellent yields, required relatively low loadings of palladium (10 ppm) and were performed under aerobic conditions. High catalyst activities with turnover frequencies of up to 20,000 h–1 were observed at 130 °C.
Keywords: olefination; catalysis; palladium; ylides; Heck reaction